2018
DOI: 10.1111/jfpp.13614
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different gaseous ozone treatments on physicochemical characteristics and shelf life of apricots stored under refrigeration

Abstract: The effect of gaseous ozone on physicochemical characteristics and shelf life of apricots stored under refrigeration was investigated. Physicochemical characteristics [weight loss, firmness, color values L*, a*, and b*, pH, titratable acidity (TA) and total soluble solids (TSS)], microbiological (fungal decay), and sensory analysis (appearance, taste, and odor) were monitored throughout storage which lasted 16 days. Ozonation [doses of 0.5, 1.0, and 1.5 mg/L (ppm) for 60 min] resulted in a significant (p < .05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…On the other hand, ozone infiltrates into cells to produce negative oxygen ions, which hinder the normal metabolism of glucose and tissue (Liu, Ma, Hu, Tian, & Sun, 2016). Panou, Karabagias, and Riganakos (2018) have found a similar phenomenon that 0.5 mg/L ozone-treated apricots scored higher on sensory evaluation than 1.0 or 1.5 mg/L treatment. Although weight loss of treated jujube was better than control group, the high dose (3 mg/L) did not apparently cutback the weight loss referred to 2.5 mg/L ozone treatment.…”
Section: Fruit Firmness Weight Loss and Colormentioning
confidence: 88%
“…On the other hand, ozone infiltrates into cells to produce negative oxygen ions, which hinder the normal metabolism of glucose and tissue (Liu, Ma, Hu, Tian, & Sun, 2016). Panou, Karabagias, and Riganakos (2018) have found a similar phenomenon that 0.5 mg/L ozone-treated apricots scored higher on sensory evaluation than 1.0 or 1.5 mg/L treatment. Although weight loss of treated jujube was better than control group, the high dose (3 mg/L) did not apparently cutback the weight loss referred to 2.5 mg/L ozone treatment.…”
Section: Fruit Firmness Weight Loss and Colormentioning
confidence: 88%
“…In our assay 'Deseo', 'Dorada', 'Maravilla', 'Murciana' and 'Rosa' reached weight loss values below 10% after 35 days at 1°C while the rest exceeded this value. Previous studies in type-dependent: the 'Precoce de Tyrinthe' variety showed weight loss values of around 4% after a 7-day cold treatment and 2 days at 20°C (Agar et al, 2006), while the 'Bebeco' variety showed weight loss values above 10% after 16 days at 4°C (Panou et al, 2018). In order to minimize fruit weight losses, the combined application of CaCl 2 and KMnO 4 could result in weight loss lower than 5% during a 10-day storage period at 28-30°C, as reported by Ishaq et al (2009).…”
Section: Evaluation Of Apricot Fruits After Different Storage Treatmentsmentioning
confidence: 89%
“…ter cold treatments of 0, 14, 28 and 42 days for different maturity states in 'Palsteyn', while Panou et al (2018) obtained 4°C.…”
Section: Evaluation Of Apricot Fruits After Different Storage Treatmentsmentioning
confidence: 93%
See 1 more Smart Citation
“…Among the treatments proposed to contain the deterioration of the crop, during post-harvest storage, one of the most promising is certainly the use of ozone, which, even in combination with low-temperature storage or packaging, can positively influence the extension of the shelf life of fruit or vegetables ( Karakosta et al., 2019 ; Panou et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%